2013
DOI: 10.1080/13596748.2013.819268
|View full text |Cite
|
Sign up to set email alerts
|

A social constructivist approach to introducing skills for employment to Foundation Degree students

Abstract: Expectations for higher education providers to produce graduates ready for the workplace have shaped provision, with the introduction of the Foundation Degree, and expectations of an employability component within higher education programmes. This paper reports on an intervention for three groups of foundation degree students, which introduces them to ideas of skills for employability. An initial evaluation was followed up two months later exploring the longer-term impact and connections within students' progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…Álvarez-González et al 2017, Pitan and Muller (2019) and Qenani et al (2014) found that university reputation has a significant direct effect on employability. The relationship between teaching staff and employability has been explored theoretically (Okolie et al, 2019;Rutt et al, 2013), and empirically using qualitative (Sin & Amaral, 2017) and quantitative (Álvarez-González et al, 2017) approaches. The relationship between matching activities with employers and employability has also been proposed by authors such as Ashraf et al (2018), Bridgstock and Jackson (2019), and Caballero et al (2014) but has not been tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Álvarez-González et al 2017, Pitan and Muller (2019) and Qenani et al (2014) found that university reputation has a significant direct effect on employability. The relationship between teaching staff and employability has been explored theoretically (Okolie et al, 2019;Rutt et al, 2013), and empirically using qualitative (Sin & Amaral, 2017) and quantitative (Álvarez-González et al, 2017) approaches. The relationship between matching activities with employers and employability has also been proposed by authors such as Ashraf et al (2018), Bridgstock and Jackson (2019), and Caballero et al (2014) but has not been tested.…”
Section: Discussionmentioning
confidence: 99%
“…Employability can be improved by means of curricular changes within study programmes (Sin & Amaral, 2017), the use of innovative pedagogies (Herbert et al, 2020;Okolie et al, 2019) such as social constructivist methods that stress participation, active learning and social interaction (Rutt et al, 2013), and the development of autonomy (Graham, 2017).…”
Section: Teaching Staffmentioning
confidence: 99%
“…Esta escisión, en opinión de Perrenoud (2008), es fruto de una división del trabajo que reposa sobre una ficción, por eso invita a la institución educativa y a los educadores a impulsar una visión más global de los aprendizajes que enfatice su utilidad y aplicación en la vida misma. Aunque, como han reconocido Cabrera et al (2016), el Proceso de Convergencia está sirviendo de detonante para estrechar lazos entre estos dos ámbitos, la superación total del desencuentro continúa siendo un desafío pendiente que dificulta el desarrollo de las competencias transversales (Rutt et al, 2013;Villarroel & Bruna, 2014). Para salvar esta situación Parris y Saville (2011) proponen, entre otras medidas: promover intercambios de conocimiento entre universidad y empresa, aumentar la presencia de la formación práctica en los planes de estudios, incorporar experiencias prácticas en empresas a la formación universitaria, reforzar los vínculos con el ámbito empresarial, contratar profesorado con experiencia en el ámbito laboral para realizar labores docentes en la universidad, y participar conjuntamente en el diseño de propuestas formativas.…”
Section: Discusión Y Conclusionesunclassified
“…Algunos de los estudios realizados hasta el momento apuntan a resultados satisfactorios y esperanzadores (Nelcy et al, 2012;Taylor y Hooley, 2014), pero un número significativo de ellos insisten en la necesidad de continuar potenciando la relación, aún deficitaria, entre universidad y mundo laboral (Rutt et al, 2013;Torres-Coronas y Vidal-Blasco, 2015).…”
Section: Introducción: Justificación Y Marco Teóricounclassified